2019
DOI: 10.1037/fam0000514
|View full text |Cite
|
Sign up to set email alerts
|

Parental autonomy support, grit, and psychological adjustment in Chinese adolescents from divorced families.

Abstract: A large body of research has shown that parental divorce is linked to youths' psychological adjustment in Western societies, but less is known about how this life event may impact on adolescents living in the Chinese cultural context, which highlights losing face and dignity. The current study aimed to examine the relationship between parental autonomy support and psychological adjustment in middle to late adolescents from divorced and intact families in China, postulating moderation by grit. Participants were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 47 publications
(71 reference statements)
6
44
0
Order By: Relevance
“…As for Chinese early adolescents, Lan and Moscardino (2019) found that, in the context of negative teacher-student relations, high levels of grit can promote Chinese early adolescents' school satisfaction and learning engagement. Indeed, highly embedded in Confucianism, Chinese culture emphasizes diligence and perseverance when facing setbacks and challenges (Lan et al, 2019a). Given these empirical findings and cultural characteristics, we proposed that grit may buffer against the association between parental harsh discipline and aggressive behavior in Chinese early adolescents.…”
Section: The Moderating Role Of Gritmentioning
confidence: 85%
See 1 more Smart Citation
“…As for Chinese early adolescents, Lan and Moscardino (2019) found that, in the context of negative teacher-student relations, high levels of grit can promote Chinese early adolescents' school satisfaction and learning engagement. Indeed, highly embedded in Confucianism, Chinese culture emphasizes diligence and perseverance when facing setbacks and challenges (Lan et al, 2019a). Given these empirical findings and cultural characteristics, we proposed that grit may buffer against the association between parental harsh discipline and aggressive behavior in Chinese early adolescents.…”
Section: The Moderating Role Of Gritmentioning
confidence: 85%
“…From a theoretical perspective, the development of aggressive behavior emerges from interactions among individual attributes and their environment (Bronfenbrenner, 1979;Jiménez and Estévez, 2017). Such an approach in the grit literature has been documented in many recent findings (e.g., Lan et al, 2019a;Lan and Radin, 2019). Statistically, given the nature of cross-sectional research design, conducting mediation analyses is not recommended, as it yields inherently misleading results (Maxwell and Cole, 2007).…”
Section: The Moderating Role Of Gritmentioning
confidence: 99%
“…Antisocial behavior was measured by the subscale of the Achenbach's Youth Self–Report version of the Child Behavior Checklist (Achenbach & Edelbrock, ), in which items are reworded in first person. This subscale has shown good test–retest reliability and criterion validity among Chinese adolescents (Lan, Marci, & Moscardino, ; Zhao, ; Zhao & Liu, ). The subscale includes nine items that measure aggressive behavior (e.g., “physically attacks people”), rule‐breaking behavior (e.g., “breaks rules at home, school, or elsewhere”), and cheating behavior (e.g., “lying or deceiving others”).…”
Section: Methodsmentioning
confidence: 99%
“…As documented by recent findings (e.g., Li and Lamb, 2015), Chinese parents now exhibit sizable warmth and autonomy support during parent-child interactions. Although parental control may be still considered one of the most common parenting styles in the Chinese society, it seems undeniable that parents have started to be more engaged and supportive of autonomy in daily child-rearing, and they often have to negotiate with their children in terms of personal goals and willingness (Li and Lamb, 2015;Lan et al, 2019b). Given these dramatic sociocultural and economic advances, we expected that parental control might have been negatively linked to students' school adjustment (Hypothesis 1).…”
Section: Parental Control and School Adjustmentmentioning
confidence: 99%
“…Although it is still a highly debated issue concerning the differential roles of these two dimensions on students' development, findings from a recent review (Credé et al, 2017) and the validation of the grit scale in a collective society (Datu et al, 2016) have supported the assertion that the construct of grit mainly focuses on perseverance of effort instead of consistency of interests. Moreover, perseverance and diligence are highly emphasized in the context of Chinese culture (Li et al, 2018;Lan et al, 2019b), and a persistent display of willpower in the face of difficulty is often regarded as a valuable individual characteristic. Given these empirical and cultural considerations, the current study explored the moderating role of grit in the association between parental control and school adjustment by focusing on perseverance only.…”
Section: The Moderating Role Of Gritmentioning
confidence: 99%